An oncogene regulating chromatin favors response to immunotherapy<subtitle>Oncogene CHAF1A and immunotherapy outcomes</subtitle> - Leqian Ying; Zhangmin Hu; Yi Lu; Qing Tao; Fen Xiong; Yongqian Shu; Yufei Yang; Xuehan Qiao; Chen Peng; Yuchun Jiang; Miao Han; Min Xu; et al. (OncoImmunology)
Many biological processes related to cell function and fate begin with chromatin alterations, and many factors associated with the efficacy of immune checkpoint inhibitors (ICIs) are actually downstream events of chromatin alterations, such as genome changes, neoantigen production, and immune checkpoint expression. However, the influence of genes as chromatin regulators on the efficacy of ICIs remains elusive, especially in gastric cancer (GC). In this study, thirty out of 1593 genes regulating chromatin associated with a favorable prognosis were selected for GC. CHAF1A, a well-defined oncogene, was identified as the highest linkage hub gene. High CHAF1A expression were associated with microsatellite instability (MSI), high tumor mutation burden (TMB), high tumor neoantigen burden (TNB), high expressions of PD-L1 and immune effector genes, and live infiltration of immune cells. High CHAF1A expression indicated a favorable response and prognosis in immunotherapy of several cohorts, which was independent of MSI, TMB, TNB, PD-L1 expression, immune phenotype and transcriptome scoring, and improved patient selection based on these classic biomarkers. In vivo, CHAF1A knockdown alone inhibited tumor growth but it impaired the effect of an anti-PD-1 antibody by increasing the relative tumor proliferation rate and decreasing the survival benefit, potentially through the activation of TGF-β signaling. In conclusion, CHAF1A may be a novel biomarker for improving patient selection in immunotherapy.